2022
DOI: 10.1186/s13287-022-02849-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stem cells-released extracellular vesicles as a next-generation cargo delivery vehicles: a survey of minimal information implementation, mass production and functional modification

Abstract: Objectives To investigate current situation of minimal information implementation highlighted by minimal information for studies of extracellular vesicles 2018 (MISEV2018) guidelines, and explore technological advances towards mass production and functional modification in aesthetic, plastic and reconstructive surgery. Methods Original articles on extracellular vesicles (EVs) of adipose stem cells (ASCs) were identified. Statistics upon minimal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 189 publications
0
11
0
1
Order By: Relevance
“…IL-6-dependent PGE2 secretion by BM-MSCs from C57BL/6 or DBA/1 mice could avert local inflammation in experimental arthritis in vivo [ 56 ]. Another study showed that healthy rat AT-MSCs-derived exosomes ameliorate diabetic osteoporosis in vivo by alleviating NLR family pyrin domain containing 3 (NLRP3) inflammasome activation [ 57 ]. Negative regulation of NLRP3 inflammasome activation hinders the secretion of IL-1β and IL-18 in osteoclasts in vitro and leads to restored bone after bone loss in animal models of streptozotocin-induced diabetic osteoporosis in vivo [ 57 ].…”
Section: The Mechanism Of Action Of Mscs and Derivative Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6-dependent PGE2 secretion by BM-MSCs from C57BL/6 or DBA/1 mice could avert local inflammation in experimental arthritis in vivo [ 56 ]. Another study showed that healthy rat AT-MSCs-derived exosomes ameliorate diabetic osteoporosis in vivo by alleviating NLR family pyrin domain containing 3 (NLRP3) inflammasome activation [ 57 ]. Negative regulation of NLRP3 inflammasome activation hinders the secretion of IL-1β and IL-18 in osteoclasts in vitro and leads to restored bone after bone loss in animal models of streptozotocin-induced diabetic osteoporosis in vivo [ 57 ].…”
Section: The Mechanism Of Action Of Mscs and Derivative Exosomesmentioning
confidence: 99%
“…Another study showed that healthy rat AT-MSCs-derived exosomes ameliorate diabetic osteoporosis in vivo by alleviating NLR family pyrin domain containing 3 (NLRP3) inflammasome activation [ 57 ]. Negative regulation of NLRP3 inflammasome activation hinders the secretion of IL-1β and IL-18 in osteoclasts in vitro and leads to restored bone after bone loss in animal models of streptozotocin-induced diabetic osteoporosis in vivo [ 57 ]. Interestingly, Gu et al (2016) reports presented that MSCs derived from gingival tissue (GMSCs) could ameliorate collagen-induced arthritis (CIA) in DBA/1 mice by facilitating the apoptosis of activated T cells through the Fas ligand (FasL)/Fas axis [ 58 ].…”
Section: The Mechanism Of Action Of Mscs and Derivative Exosomesmentioning
confidence: 99%
“…Many studies have also reported enhanced therapeutic efficacy of adipose stem cell released extracellular vesicles and exosomes are being used to enhance wound healing in DFUs [ 61 , 62 , 63 ]; it is imperative to further investigate the strategies to enhance the therapeutic efficacy of stem cells and their synergistic or additive effects in a combinational approach to promote angiogenesis and wound healing in chronic non-healing DFUs. In-depth research involving exosomes (EVs) isolated from stem cells is also important because EVs isolated from different types of stem cells may have differential effects on angiogenesis and wound healing as reported by Pomatto et al [ 64 ] that EVs isolated from bone marrow and adipose mesenchymal stem cells have differential therapeutic effects on wound healing and angiogenesis.…”
Section: Stem-cell Derived Exosomes and Combinational Strategies To E...mentioning
confidence: 99%
“…Particularly, EVs derived from adipose tissue-derived stem cells(ADSCs-EVs) can uniquely mediate specific target cells through their bio-active cargos such as microRNAs ( 18 ). The research about ADSCs-EVs has been surging dramatically in the past 5years, mainly in tissue repair field ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%